Rasterstereographic Analysis of Lateral Shift in Patients with Lumbar Disc Herniation: A Case Control Study - Britta K. Krautwurst; Jürgen R. Paletta; Sylvia Mendoza; Adrian Skwara; Melvin Mohokum (Advances in Orthopedics)
Objective. Detection of a lateral shift (LS) in patients with diagnosed disc herniation compared to healthy controls. Summary of Background Data. A specific lateral shift (LS) pattern is observed in patients with disc herniation and low back pain, as shown in earlier studies. Methods. Rasterstereography (RS) was used to investigate the LS. Thirty-nine patients with lumbar disc herniation diagnosed by radiological assessment and low back pain and/or leg pain (mean age 48.2 years, mean BMI 28.5, 28 males and 11 females) and 36 healthy controls (mean age 47.4 years, mean BMI 25.7, 25 males and 11 females) were analysed. LS, pelvic tilt, pelvic inclination, lordotic angle, and trunk torsion were assessed. Results. The patient group showed a nonsignificant increase in LS, that is, 5.6 mm compared to the healthy controls with 5.0 mm (p = 0.693). However, significant differences were found between groups regarding pelvic tilt in degrees (patients 5.9°, healthy controls 2.0°; p = 0.016), trunk torsion (patients 7.5°, controls 4.5°; p = 0.017), and lordotic angle (patients 27.5°, healthy controls 32.7°; p = 0.022). The correlation between pain intensity and the FFbH-R amounted 0.804 (p = < 0.01), and that between pain intensity and the pain disability index was 0.785 (p < 0.01). Discussion. Although some studies have illustrated LS with disc herniation and low back pain, the present findings demonstrate no significant increase in LS in the patient group compared to healthy controls. Conclusion. The patients with lumbar disc herniation did not demonstrate an increased LS compared to healthy controls. Other parameters like pelvic tilt and inclination seemed to be more suitable to identify changes in posture measured by RS in patients with low back pain or disc herniation.